New technology-based firms in the new millennium. Vol. 10 - Oakey, R. P. (Emerald, 2013)
This volume is the latest edition of an international edited book series based on the formation and growth problems of High Technology Small Firms (HTSFs) begun in 1993. This body of work is unique, and maps the evolution of research in this area through almost two decades of academic research and government policy towards a sector that is the key to future prosperity of developed and developing notational economies throughout the world.
Keywords: High technology industries.; New business enterprises.; elektronické knihy; electronic books